The role and regulation of insulin-like peptide 3 (INSL3) in the female reproductive system - Dai, Yanzhenzi (2017)
The peptide hormone Insulin-like peptide 3 (INSL3) shows important roles in the reproductive system. In the male, the testicular Leydig cell peptide INSL3 is involved in fetal testis descent and sperm maturation during the adulthood. In females of reproductive age INSL3 is mainly produced by the ovarian follicular theca interna cells. The current project aims to explore the detailed actions of INSL3 in the female reproductive system. Firstly, the secretion pattern of the INSL3 peptide in the serum of young women and women attending an infertility clinic was assessed. The serum levels of INSL3 peptide appeared to increase during the follicular phase, decrease during the luteal phase, and drop to a nadir at menses. The secretion pattern corresponded to the growth of antral follicles within a follicular wave. Pathological conditions leading to an alteration of the antral follicle count, such as polycystic ovarian syndrome and low ovarian reserve, were accompanied by an increase or decrease in the serum INSL3 level, respectively. The bovine system was adopted and validated as a model for the human in regard to the follicular production of INSL3, as the secretion pattern for INSL3 in bovine serum through estrous cycles was similar to that in women. Primary bovine theca interna cells were then used to study the regulation of the INSL3 gene and its secreted peptide products. At both peptide and mRNA levels INSL3 production could be up-regulated by progesterone receptor signalling. Together with the analysis of the transcriptional activity of the bovine INSL3 gene promoter, it could be shown that estradiol (E2) – estrogen receptor alpha (ERα) signalling stimulated and E2-ERß signalling decreased INSL3 production. Dihydrotestosterone (DHT) acting through the androgen receptor (AR) and androstenedione (A4) probably acting through ERα and/or ERß both contribute to regulation of INSL3 production. Moreover, luteinising hormone (LH) from the anterior pituitary also influenced the INSL3 production, with the downstream pathway from low level LH stimulation probably involving synergy between cAMP-PKA and ER signalling. The potential target of INSL3 was also identified in the female bovine reproductive system; full-length transcripts for the INSL3 receptor, RXFP2, were detectable in ovarian theca interna cells, in oocytes, as well as in the myometrium. Meanwhile, full-length transcripts for the closely related receptor, RXFP1, were detected in theca interna cells, endometrium and in myometrium, although the gene encoding the ligand for this receptor, relaxin, has been deleted during ruminant evolution. When transfecting DNA expression plasmids encoding the individual RXFP2 and RXFP1 receptors into HEK293T cells, the expressed bovine RXFP2 could be activated by bovine and human INSL3 (EC50 = 0.7 & 0.6nM) and porcine and human relaxin (EC50 = 10.5 & 27.3nM). The expressed bovine RXFP1 could be activated by porcine and human relaxin (EC50 = 10.8 & 48.7nM) and human relaxin 3 (EC50 = 97.9nM). Functional analysis showed that bovine myometrial cells were able to respond to both exogenous relaxin and INSL3, whereas theca interna cells could respond to INSL3 only. Together, however, these experiments support the view that endogenous RXFP2 and RXFP1 are both fully functional in the bovine even though the primary ligand for the latter is missing. The results showed that for the female INSL3 is mainly produced by the theca interna cells of antral follicles, and is thus a potential biomarker of ovarian functionality. The expression of INSL3 can be regulated by sex steroid hormones in an auto/paracrine manner, as well as by LH in an endocrine manner. In conclusion, the INSL3-RXFP2 system acts in follicles and probably also the uterus to enable and orchestrate female reproductive physiology.